METHODOLOGY OF TEACHING SPORTS AND MOVING GAMES (Archive of Conferences, 2021)
Physical education is an integral part of the national culture of our people. A compass that guides young people to both physical and spiritual maturity. The honor and prestige of the country is determined by the achievements of such young people in the international arena. As an ambassador of sports and friendship, his role in the development of the country is invaluable. In this regard, of course, rely on the new pedagogical technologies, as well as the experience of qualified educators, coaches, trainers. The article covers the theoretical knowledge that undergraduate students need to acquire in the field of physical education, as well as practical advice for students to practice independently during and after classes.